Answer:
x=3
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
2(x−5)+8=4
(2)(x)+(2)(−5)+8=4(Distribute)
2x+−10+8=4
(2x)+(−10+8)=4(Combine Like Terms)
2x+−2=4
2x−2=4
Step 2: Add 2 to both sides.
2x−2+2=4+2
2x=6
Step 3: Divide both sides by 2.
2x/2 = 6/2
x=3
Step 1: Add 3x to both sides.d−3x+3x=−9+3xd=3x−9 = ANSWER
Can you possibly help me on my recent question?
1st number = n
2nd number = n+1
3rd number = n+2
sum of the squares of 3 consecutive numbers is 116
n² + (n+1)² + (n+2)² = 116
n² + (n+1)(n+1) + (n+2)(n+2) = 116
n² + [n(n+1)+1(n+1)] + [n(n+2)+2(n+2)] = 116
n² + n² + n + n + 1 + n² + 2n + 2n + 4 = 116
n² + n² + n² + n + n + 2n + 2n + 1 + 4 = 116
3n² + 6n + 5 = 116 Last option.
So, let's start off with explaining what these different questions mean;
y = |x + c| Shifts the graph c units left.
y = |x - c| Shifts the graph c units right.
y = |x| + c Shifts the graph c units up.
y = |x| - c Shifts the graph c units down.
(0,0) Is the starting point on any graph like this. So, determine the answer by going through the list of answers.
I believe the answer is y = 2x.
I would like to know if I am wrong so contact me!!
Answer:
y=2x-4
Step-by-step explanation:
well first you have to move the -8x to the other side where the -16 is. by doing so, the -8x will turn into a POSTIVE 8x. than your problem should look like (4y=8x-16). now that your problem is like that, you want "y" to be alone. so, you divide the 4 by every number. (so you would do 4y/4, 8x/4, and -16/4). than your final product would be: y=2x-4